Phenotypic and Genotypic Characterization of Foliar Bleaching and Regreening Associated with Heat and Light Stress in Pelargonium peltatum - Bowdish, Paige (My University, 2026)
Ivy geranium (Pelargonium peltatum) develops ivory foliage under high temperature and light stress. Occurrence, severity, and patterns of development and remission of the disorder differ among cultivars. A two-phase, split-plot greenhouse experiment with two environments [“elevated temperature and light stress” (ETL) with high average daily temperature (ADT; 33.8oC) and daily light integral (DLI; 15.3 moles.day-1) versus Control with 27.6oC ADT and 9.8 moles.day-1 DLI] and sub-plots of 12 Pelargonium genotypes (n=6 with 2 pots per e.u.) was conducted during summer 2025. Phenotypic observations and leaf greenness measured with a SPAD meter were taken on mature, juvenile, immature, and newly emerged leaves that developed in the treatment environments. After foliar bleaching occurred in the ETL environment (phase I, 26 d), these plants were moved to the Control environment to observe and measure regreening (phase II, 23 d). Bleaching occurred not only in foliage, but also peduncle and sepals of some cultivars. Leaves near the meristem were most susceptible to foliar bleaching under ETL. The most tolerant cultivars differed in pattern of bleaching and leaf morphology, including lamina venation. Extent of regreening was dependent on leaf developmental stage when ETL occurred, and foliage was unlikely to regreen if the leaf matured during ETL or developed any necrosis. These observations inform further research to identify gene(s) responsible for foliar bleaching under ETL.  Genomic analysis was conducted on ‘Ivy League Red’ and ‘Ivy League Hot Coral’, representing cultivars tolerant and sensitive to ETL, respectively. The gene protochlorophyllide oxidoreductase (LPOR), which is active in chlorophyll biogenesis, was targeted. As the genome of Pelargonium is not fully sequenced, comparative sequence analysis from genomically similar species, including Theobroma cacao, Jatropha curcas, Citrus sinensus, and Vitis vinifera, were used to reconstruct a partial sequence of LPOR isotype C to examine genetic expression differences between the tolerant and sensitive cultivars. Semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) for the PORC transcript showed that expression patterns of PORC differed between the two cultivars, suggesting distinct responses to heat stress. In ‘Ivy League Red’, the transcript of PORC was detectable before heat exposure, suggesting a priming state. After heat treatment, its expression decreased. In ‘Ivy League Hot Coral,’ the PORC transcript is initially low and only increases after foliar bleaching begins, a response that is likely insufficient to prevent the bleaching phenotype. These opposite expression patterns contribute to our understanding of the underlying physiology of foliar bleaching.
Keywords: Environmental Stress; Heat and light stress plant bleaching; Unsequenced genome; Pelargonium (ivy geranium); Chlorophyll; Crop improvement